Taxonomy as a hypothesis: testing the status of the Bermuda buckeye butterfly Junonia coenia bergi (Lepidoptera: Nymphalidae). (19th October 2016) - PETERS, MELISSA J.; MARCUS, JEFFREY M.
Abstract: Species determination and definition in eukaryotes have traditionally been based on morphology, with little focus on genetic differentiation. Molecular methods allow for the independent assessment of morphology‐based taxonomic hypotheses. Three criteria used to define a full species for taxonomic purposes are morphological distinction, formation of a monophyletic lineage, and reproductive isolation. Junonia butterflies (Nymphalidae) are becoming an important experimental model system, but the taxonomy of many New World Junonia species is unclear. One of these species is J. coenia, which contains the subspecies J. coenia coenia, J. coenia grisea and J. coenia bergi . Previous studies suggest that J. coenia grisea may meet the criteria for full species status. Therefore, we evaluated the geographically isolated and rarely studied Bermuda buckeye butterfly J. coenia bergi to determine if it was similarly distinct. Physical examination of specimens and phylogenetic and population genetic analyses of mitochondrial cytochrome c oxidase subunit I, nuclear wingless, and complete mitochondrial genome sequences suggest that while J. coenia bergi is smaller in body size than many Junonia and has distinctive ventral hindwing colouration, it does not form a monophyletic lineage and shows indications of continued gene flow with North American mainland J. coenia coenia populations. Thus, J. coenia bergi does not meet the criteria for full species designation, but geographic isolation, morphological distinctiveness, and cultural importance suggest that it remain recognized as a subspecies of J. coenia . Similar analyses will be useful for addressing further taxonomic questions in Junonia and other taxa, especially where morphology‐based taxonomic determinations are ambiguous.